Composition of dense beryllium plasmas - Gabdullin, M. T.; Ramazanov, T. S.; Akhtanova, G. B.; Redmer, R. (Recent Contributions to Physics, 2013)
In the present paper the composition of dense beryllium plasma by solving the Saha equations with corrections due to non-ideality was investigated. The lowering of the ionization potentials is calculated on the basis of effective potentials by taking into account screening and quantum diffraction effects. The contribution from the polarization of neutral atoms was calculated via the linearized virial coefficient for the interaction of electrons with atoms. The number density varies in the range 18 23 3 10 10 e n cm   and the temperature domain considered here is 4 6 T   10 10 K. In considered range of density and temperature the plasma changes from atom state to full ionized plasma with the maximum degree of ionization. The ionization degree was determined as relation between the number density of free electrons to number density of nuclear in plasma. The composition of dense beryllium plasma, which consists of electrons, ions, and atoms, was considered on the basis of chemical model. Obtained system of nonlinear Saha equations was calculated by numerical methods.